PENGARUH KEPERCAYAAN, IKLAN, PERSEPSI RESIKO TERHADAP KEPUTUSAN PEMBELIAN DI SITUS SHOPEE PADA KONSUMEN KELURAHAN LUBUK BUAYA - Febsri Susanti; Chintya Mulyani (LP2M Universitas Bina Bangsa, 2022)
The purpose of study was to determine the effect of trust, advertising, risk percepstion on purchasing decisions on shopee to cnsumers in kelurahan lubuk buaya.This research was conducted with a total of 95 consumersin this study were with a technique slovin. Analysis of the data used is multiple linear regression analysis. Partial test results show that there is a positive and significant influence of trust of origin on purchasing decisions, there is a no effect and no significant influence of advertising on purchasing decisions, and there is a positive and significant influence of risk perception on purchasing decisions